Modernization of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Program: Rationale and Overview of the THIS-WIC (Telehealth Intervention Strategies for WIC) Project - Catherine Wright; Pascasie Adedze; Alice Ammerman; Lauren Au; Alan Barnosky; Jonathan Blitstein; Karen Castellanos-Brown; Sheryl Cates; Madhur Chandra; Kenneth Kwan Ho Chui; Katharine Clarke; Christina Economos; et al. (Journal of Nutrition Education and Behavior, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Constraining the duration of the southern Gondwana Irati-Whitehill Sea through cyclostratigraphy and its relation with deep-time astronomical solutions - Aurélio F. Silva; Thiago P. Santos; Pedro L.A. Xavier; Norberto Dani; Cesar L. Schultz; Marcus V.D. Remus; Ruy P. Philipp; Raysa M. Rocha; Daniel R. Franco; Marco António L. da Silva (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Superficial scald development in ‘Granny Smith’ and ‘Nicoter’ apples: The role of key volatile compounds when fruit are stored under dynamic controlled atmosphere - Jossiê Zamperetti Donadel; Fabio Rodrigo Thewes; Luana Ferreira dos Santos; Erani Eliseu Schultz; Magno Roberto Pasquetti Berghetti; Vagner Ludwig; Juliana Mesadri; Bruna Klein; Flavio Roberto Thewes; Suele Fernanda Prediger Schmidt; Vanderlei Both; Auri Brackmann; et al. (Food Research International, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Stressing environmental conditions in the “petrified forest” from the Mata Sequence in the Triassic context of the Paraná Basin - Ângela Cristine Scaramuzza dos Santos; Margot Guerra-Sommer; Eduardo Guimaraes Barboza; Isabela Degani-Schmidt; Anelise Marta Siegloch; Carlos Eduardo Lucas Vieira; Daniel Triboli Vieira; Tatiana Pastro Bardola; César Leandro Schultz (Journal of South American Earth Sciences, 2023)

Soil, water and nutrient loss under simulated rainfall patterns in an area fertilised with chicken litter - Amanda Sales Alves; Nivaldo Schultz; Bruno Antonio Augusto Faria Conforto; Everaldo Zonta; Daniel Fonseca de Carvalho (Journal of Hydrology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Microbiome Development of Seawater-Incubated Pre-production Plastic Pellets Reveals Distinct and Predictive Community Compositions - Christopher S. Ward; Zoie Diana; Kate Meicong Ke; Beatriz Orihuela; Thomas P. Schultz; Daniel Rittschof (Frontiers in Marine Science, 2022)
Plastics of various chemistries pollute global water bodies. Toxic chemicals leach with detrimental and often unpredictable impacts on the surrounding ecosystems. We found that seawater leachates of plastic pre-production pellets from 7 recycle categories are acutely toxic to stage II barnacle nauplii; lethal concentration 50 (LC50s) were observed in 24-h leachates from dilutions ranging from 0.007 to 2.1 mg/mL of seawater. Based on previous observations that macro-organismal settlement on fouling management coatings of various toxicities can be used to predict the toxicity of the coating, we hypothesized that interaction of plastic pre-production pellets with emerging microbiomes would exhibit patterns indicative of the chemistry at the pellet surface. We used amplicon sequencing of bacterial 16S ribosomal RNA genes to characterize the microbiomes that developed from 8 through 70 days on pellets exposed to the same flowing ambient seawater. Diversity and composition of the microbiomes colonizing plastic pellets changed over time and varied with plastic type. Microbial taxa belong to taxonomic groups known to consume hydrocarbons, to be prevalent following marine oil spills, or to live on fouling management surfaces. Microbiomes were still distinct between plastic types at Day 70, suggesting that differences in the physicochemical characteristics of the underlying plastics continue to exert variable selection of surface microbial communities. A random forest-based sample classifier correctly predicted 93% of plastic types using microbiome compositions. Surface microbiomes have promise for use in forensically identifying plastic types and potential toxicities.

Compositional and Functional Microbiome Variation Between Tubes of an Intertidal Polychaete and Surrounding Marine Sediment - Matthew Fuirst; Christopher S. Ward; Caroline Schwaner; Zoie Diana; Thomas F. Schultz; Daniel Rittschof (Frontiers in Marine Science, 2021)
The decorator worm Diopatra cuprea , a tube-forming marine polychaete common to intertidal and shallow subtidal waters, modifies habitats it occupies through microreef construction and algal gardening. While several studies have demonstrated that decorator worm tubes are hotspots of biogeochemical activity (i.e., nitrogen and sulfur cycling), it is still largely unclear whether the tube microbiome differs compositionally from the surrounding sediment and what distinct functional processes tube microbiomes may have. To address these unknowns, this study analyzed the bacterial communities of D. cuprea tubes and surrounding sediments using high-throughput 16S rRNA gene amplicon sequencing. Tubes and sediments were sampled at three sites along an anthropogenic stress gradient within the Newport River Estuary to also assess geographic variation of tube microbiomes and the possible influence of human disturbance. We found a clear distinction in the microbial community composition and diversity between tubes and surrounding sediment. Tube microbiomes were significantly enriched for the phyla Bacteriodetes, Actinobacteria, Verrucomicrobia, Deferribacteres, Latescibacteria, and Lentisphaerae. Chloroplast sequences of macroalgae and grass species were consistently abundant in tubes and nearly absent in surrounding sediment. Functional annotation of prokaryotic taxa (FAPROTAX)-based functional predictions suggested that tube microbiomes have higher potentials for aerobic chemoheterotrophy, sulfur compound respiration, nitrate reduction, methylotrophy, and hydrocarbon degradation than surrounding sediments. Tube microbiomes vary across sites, though dissimilarity is comparatively low compared to tube-to-sediment differences. Contrary to our hypothesis, the tubes at the most highly impacted site had the highest microbial diversity [i.e., amplicon sequence variant (ASV) richness and Shannon’s diversity], yet tubes from the medium impacted site actually had the lowest microbial diversity. Our findings show that D. cuprea tubes support a microbiome that is significantly distinct in composition and function from the surrounding sediment. Diopatra cuprea tubes appear to create unique microhabitats that facilitate numerous microbially-mediated biogeochemical processes in the marine benthic environment.

Exploring the Diversity of the Marine Environment for New Anti-cancer Compounds - Divya L. Dayanidhi; Beatrice C. Thomas; Joshua S. Osterberg; Mallissa Vuong; Giselle Vargas; Sarah K. Kwartler; Emma Schmaltz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Daniel Rittschof; William C. Eward; Christopher Roy; et al. (Frontiers in Marine Science, 2021)
Marine ecosystems contain over 80% of the world’s biodiversity, and many of these organisms have evolved unique adaptations enabling survival in diverse and challenging environments. The biodiversity within the world’s oceans is a virtually untapped resource for the isolation and development of novel compounds, treatments, and solutions to combat human disease. In particular, while over half of our anti-cancer drugs are derived from natural sources, almost all of these are from terrestrial ecosystems. Yet, even from the limited analyses to date, a number of marine-derived anti-cancer compounds have been approved for clinical use, and several others are currently in clinical trials. Here, we review the current suite of marine-derived anti-cancer drugs, with a focus on how these compounds act upon the hallmarks of cancer. We highlight potential marine environments and species that could yield compounds with unique mechanisms. Continued exploration of marine environments, along with the characterization and screening of their inhabitants for unique bioactive chemicals, could prove fruitful in the hunt for novel anti-cancer therapies.

Habitat associations of settlement-stage crown-of-thorns starfish on Australia’s Great Barrier Reef - Jennifer C. Wilmes; Daniel J. Schultz; Andrew S. Hoey; Vanessa Messmer; Morgan S. Pratchett (Coral Reefs, 2020)

Toward a Common Understanding of Ocean Multi-Use - Maximilian Felix Schupp; Martina Bocci; Daniel Depellegrin; Andronikos Kafas; Zacharoula Kyriazi; Ivana Lukic; Angela Schultz-Zehden; Gesche Krause; Vincent Onyango; Bela H. Buck (Frontiers in Marine Science, 2019)

The effects of disproportional load contributions on quantifying vegetated filter strip sediment trapping efficiencies - Heather E. Gall; Daniel Schultz; Tamie L. Veith; Sarah C. Goslee; Alfonso Mejia; Ciaran J. Harman; Cibin Raj; Paul H. Patterson (Stochastic Environmental Research and Risk Assessment, 2018)

3D Cosmic Ray Muon Tomography from an Underground Tunnel - Elena Guardincerri; Charlotte Rowe; Emily Schultz-Fellenz; Mousumi Roy; Nicolas George; Christopher Morris; Jeffrey Bacon; Matthew Durham; Deborah Morley; Kenie Plaud-Ramos; Daniel Poulson; Diane Baker; et al. (Pure and Applied Geophysics, 2017)

Analytical approaches to support current understanding of exposure, uptake and distributions of engineered nanoparticles by aquatic and terrestrial organisms - Carolin Schultz; Kate Powell; Alison Crossley; Kerstin Jurkschat; Peter Kille; A. John Morgan; Daniel Read; William Tyne; Elma Lahive; Claus Svendsen; David J. Spurgeon (Ecotoxicology, 2015)

Human disturbance causes the formation of a hybrid swarm between two naturally sympatric fish species - Daniel J. Hasselman; Emily E. Argo; Meghan C. McBride; Paul Bentzen; Thomas F. Schultz; Anna A. Perez‐Umphrey; Eric P. Palkovacs (Molecular Ecology, 2014)
Most evidence for hybrid swarm formation stemming from anthropogenic habitat disturbance comes from the breakdown of reproductive isolation between incipient species, or introgression between allopatric species following secondary contact. Human impacts on hybridization between divergent species that naturally occur in sympatry have received considerably less attention. Theory predicts that reinforcement should act to preserve reproductive isolation under such circumstances, potentially making reproductive barriers resistant to human habitat alteration. Using 15 microsatellites, we examined hybridization between sympatric populations of alewife ( Alosa pseudoharengus ) and blueback herring ( A. aestivalis ) to test whether the frequency of hybridization and pattern of introgression have been impacted by the construction of a dam that isolated formerly anadromous populations of both species in a landlocked freshwater reservoir. The frequency of hybridization and pattern of introgression differed markedly between anadromous and landlocked populations. The rangewide frequency of hybridization among anadromous populations was generally 0–8%, whereas all landlocked individuals were hybrids. Although neutral introgression was observed among anadromous hybrids, directional introgression leading to increased prevalence of alewife genotypes was detected among landlocked hybrids. We demonstrate that habitat alteration can lead to hybrid swarm formation between divergent species that naturally occur sympatrically, and provide empirical evidence that reinforcement does not always sustain reproductive isolation under such circumstances.

Age-dependent visuomotor performance and white matter structure: a DTI study - Kathrin Koch; Gerd Wagner; Claudia Schachtzabel; C. Christoph Schultz; Daniel Güllmar; Jürgen R. Reichenbach; Heinrich Sauer; Ralf G. M. Schlösser (Brain Structure and Function, 2013)

Development of twenty-four novel microsatellite markers for the freshwater crayfish, Geocharax gracilis, using next generation sequencing - Craig D. H. Sherman; Daniel Ierodiaconou; Annalise M. Stanley; Kim Weston; Michael G. Gardner; Mark B. Schultz (Conservation Genetics Resources, 2012)

New stem-sauropodomorph (Dinosauria, Saurischia) from the Triassic of Brazil - Sergio F. Cabreira; Cesar L. Schultz; Jonathas S. Bittencourt; Marina B. Soares; Daniel C. Fortier; Lúcio R. Silva; Max C. Langer (The Science of Nature, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Sea‐level changes and palaeo‐ranges: reconstruction of ancient shorelines and river drainages and the phylogeography of the Australian land crayfish Engaeus sericatus Clark (Decapoda: Parastacidae) - MARK B. SCHULTZ; DANIEL A. IERODIACONOU; SARAH A. SMITH; PIERRE HORWITZ; ALASTAIR M. M. RICHARDSON; KEITH A. CRANDALL; CHRISTOPHER M. AUSTIN (Molecular Ecology, 2008)
Historical sea levels have been influential in shaping the phylogeography of freshwater‐limited taxa via palaeodrainage and palaeoshoreline connections. In this study, we demonstrate an approach to phylogeographic analysis incorporating historical sea‐level information in a nested clade phylogeographic analysis (NCPA) framework, using burrowing freshwater crayfish as the model organism. Our study area focuses on the Bass Strait region of southeastern Australia, which is marine region encompassing a shallow seabed that has emerged as a land bridge during glacial cycles connecting mainland Australia and Tasmania. Bathymetric data were analysed using Geographical Information Systems (GIS) to delineate a palaeodrainage model when the palaeocoastline was 150 m below present‐day sea level. Such sea levels occurred at least twice in the past 500 000 years, perhaps more often or of larger magnitude within the last 10 million years, linking Victoria and Tasmania. Inter‐locality distance measures confined to the palaeodrainage network were incorporated into an NCPA of crayfish ( Engaeus sericatus Clark 1936) mitochondrial 16S rDNA haplotypes. The results were then compared to NCPAs using present‐day river drainages and traditional great‐circle distance measures. NCPA inferences were cross‐examined using frequentist and Bayesian procedures in the context of geomorphological and historical sea‐level data. We found distribution of present‐day genetic variation in E. sericatus to be partly explained not only by connectivity through palaeodrainages but also via present‐day drainages or overland (great circle) routes. We recommend that future studies consider all three of these distance measures, especially for studies of coastally distributed species.

Drainage under increasing and changing requirements - Bart Schultz; Daniel Zimmer; Willem F. Vlotman (Irrigation and Drainage, 2007)

Antibodies from a DNA peptide vaccination decrease the brain amyloid burden in a mouse model of Alzheimer?s disease - Jan G. Schultz; Ulrich Salzer; M. Hasan Mohajeri; Daniel Franke; Jochen Heinrich; Jovan Pavlovic; M. Axel Wollmer; Roger M. Nitsch; Karin Moelling (Journal of Molecular Medicine, 2004)